Pelatihan Legislasi Peraturan Desa bagi Perangkat Desa Tlobo, Desa Karangsari dan Kelompok Peduli Waduk Jlantah Kecamatan Jatiyoso Kabupaten Karanganyar Village Regulation Legislation Training for Tlobo Village Apparatus, Karangsari Village and Jlantah Re - Sukarno, Karmila Sari; Chasanah, Immawati Uswatun; Arsetyo, Yulio Iqbal Cahyo; Nurviana, Reky; Buana, Nimas; Evi, Safira; Irawan, Andrie (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2024)
The training on village regulation legislation for the officials of Tlobo Village, Karangsari Village, and the Waduk Jlantah Care Group aimed to enhance their capacity in drafting and implementing quality village regulations. This program focused on strengthening participants' understanding of the legislative process while encouraging community participation in decision-making. The methods employed included interactive lectures, case studies, and public consultation simulations, which proved effective in improving participants' comprehension. Evaluation results indicated a significant increase, with participants' understanding scores rising from 45% in the pre-test to 85% in the post-test. Additionally, 80% of the draft village regulations produced by participants met the standards, with 30% rated as very good. However, challenges remain in the precise use of legal language and conflict management during public consultation processes. Therefore, future training sessions should emphasize these aspects. This training is expected to serve as a catalyst for the development of tourism villages based on Waduk Jlantah, creating regulations that support sustainable resource management. With a participatory and contextual approach, it is hoped that synergy between village governments and communities can be established, resulting in village regulations that are responsive to local needs and contribute to community welfare. Ultimately, the enhancement of legislative capacity at the village level is anticipated to support better and more transparent development in the future.